Securing the Vista environment - Gregory, Peter H. (O'Reilly, 2007)
"Securing the Vista Environment" takes you on a quick tour of the most significant security features in Vista, Microsoft's first revision of Windows in almost six years. You'll get background on threats and vulnerabilities that will make you think differently about security. Security is more than just the technology and configurations--it's about how we use the system that makes it secure or not. Then we'll cover Vista's security features, from user privileges to Windows Defender, User Account Control, and BitLocker, as well as strategies for protecting your information from unwanted disclo
Print version record
Keywords: Microsoft Windows (Computer file); Computer security; Computer Security; Sécurité informatique; PHILOSOPHY; Essays; PHILOSOPHY; Reference